Gathering space: landscape and enclosure in the early neolithic of southern Britain - Durkin, DMJ (2019)
This thesis centres around a form of early Neolithic architecture described as the causewayed enclosure. Though detailed research has focused on the material recovered from their ditches, much of their wider interpretation is based on, or has roots in, the territorial models produced in the 1970s. This study draws on theoretical approaches including, Affordance, Proxemics, Phenomenology, and Agency to challenge these earlier interpretations.